Optimalisasi Kinerja Karyawan Melalui Lingkungan Kerja, Reward, dan Punishment di STIKES Surya Global Yogyakarta - Priyanto, Muhammad Arif; Sutanto, Aftoni; Hidayat, Abdul Choliq (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
The purpose of this study is to find out how employee performance at STIKES Surya Global Yogyakarta is affected by the work environment, rewards and punishments. The benefit of this research is to provide a new scientific understanding of human resource management, specifically the extent of employee performance in private universities. This kind of research falls under the category of quantitative research. This study used a population of 60 permanent employees of the Yogyakarta Surya Global College of Health Sciences. Using questionnaires and the Issac and Michael approach, this study selected 56 respondents with a margin of error of 1%. The data analysis approach of this study includes the use of smartPLS 3 software to support multiple linear regression analysis, determination coefficient test (R2), and partial significance test (T test). The Likert scale questionnaire was used as a research instrument. This study obtained the following results: 1) Employee performance at STIKES Surya Global Yogyakarta is positively and significantly influenced by the work environment with a significance value of 0.008 and a t-statistical value of 2.667; 2) Employee performance at STIKES Surya Global Yogyakarta was positively and significantly influenced by rewards with a significance value of 0.000 and a t-statistical value of 6.869; and 3) Employee performance at STIKES Surya Global Yogyakarta was positively and significantly influenced by punishment with a significance value of 0.000 with a t-statistic of 4.754. Employee performance can be affected by creating a positive working environment with the implementation of appropriate rewards and punishments. The Work Environment, Reward, and Punishment factors at STIKES Surya Global Yogyakarta contributed 78.6%, based on the R square score or determination coefficient of 0.786; While the remaining 21.4% was influenced by other variables that were not studied in this study